A Groundwater Quality Monitoring System Using IoT and GPS - Sally Lerian Edward; Riri Jonuarti; Mona Berlian Sari (Research on Instrumentation, 2025)
Conventional groundwater quality monitoring methods are often inefficient due to delays in data acquisition and limitations in spatial location tagging and automated data management. This study aims to develop a portable monitoring system based on NodeMCU ESP32 that is capable of measuring temperature, pH, TDS, and conductivity parameters in situ. The main innovation of this tool lies in the integration of a GPS module for mapping sample collection locations, automatic data storage to spreadsheets via an IoT platform, and a visual LED warning system calibrated according to the quality standards of PerMenKes No. 32 of 2017. Test results show that the system functions optimally with parameter accuracy levels reaching 95-99% and an error rate below 5% compared to standard measuring instruments. This system offers an effective solution for rapid, accurate, and digitally documented groundwater quality mapping